Mosquito breeding status in drains of Moulvibazar municipality area, Sylhet, Bangladesh - Bagum, Musammath Amina; Kabir Chowdhury, Md Ashek; Rahman, G M Saifur (Bangladesh Journal of Zoology, 2025)
Mosquitoes can be vectors of several infectious and life-threatening diseases including bancroftian filariasis, which is endemic in Eastern hilly and forest parts of Bangladesh together with Moulvibazar district. To assess its vector breeding situation a yearlong (September 21 to August 22) intensive survey was conducted in different drains in the nine administrative wards in the municipality areas of Moulvibazar. Three species of mosquito immature were identified in the stagnant water of different types of drain habitats. Among them, Culex quinquefasciatus was the dominant species (88.4%) followed by Armigeres sp (11.2%) and Cx. tritaeniorhynchus (0.2%). The highest population was found in Drain-4 in Ward-1 and the fewest mosquito larvae were observed in Drain-55 under Ward 6. ANOVA suggested that mosquito immature varied significantly in different months in different Wards. Pearson correlation analysis indicated rainfall and relative humidity are the most important meteorological factors influencing the occurrence of mosquito-immature populations. Specifically, water temperature is positively correlated with total immature (r = 0.645, p = 0.000), Cx. quinquefasciatus (r = 0.470, p = 0.000) and with Armigeres sp (r = 0.271, p = 0.000). Water PH has a positive correlation with Armigeres sp (r = 0.528, p = 0.000), but a negative correlation with Cx. quinquefasciatus (r = -.380**, p = 0.000). Water depth has shown a negative correlation with Cx. quinquefasciatus (r = -.413**, p = 0.000) and Armigeres sp (r = -.194**, p = 0.000). Furthermore, average temperature is positively correlated with total rainfall (r = 0.631*, p = 0.028) and rainfall days (r = 0.770, p = 0.003), whereas total mosquito immature is negatively correlated with total rainfall (p = -.585*, p = 0.046), rainfall of days (r = -0.673*, p = 0.016) and humidity (r = -.922** p = 0.000). These findings will provide a basic guideline to plan future mosquito control operations in the present study area. Bangladesh J. Zool. 52(3): 247-267, 2024